Anti-Mitoticpotential Identification of Nyale (Eunice sp.) in The Tourism Area of Kuta Beach, Lombok Island, West Nusa Tenggara - Arjita, Putu Dedy; Rozikin, Rozikin; Adnyana, Gede Angga; Anulus, Ayu; Utami, Sukandriani; Widiyanto, Aris; Putri, Santy Irene (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: BauNyale festival is a Lombok tradition that originated in the Kuta beach tourism area in Central Lombok. The locals of Lombok Island gathered in this location to harvest marine worms known as Nyale (Eunice sp.). The ability of marine worms to act as anticancer agents has received little attention in Indonesia. AIM: This study aimed to examine the biomolecules compounds of Nyale as antimitotic candidates. METHODS: This was a preliminary study using post-test only with a control group design. The sample of this study was Nyale (Eunice sp.), and sea urchin (Tripneustes ventricosus) collected from Kuta beach, Central Lombok. The Nyale was extracted with 96% ethanol as the solvent. Gas Chromatography-Mass Spectrometry (GCMS) was used to determine the content of bioactive compounds. Sea urchin embryos were divided into four treatment groups (control; 10 mg, 100 mg, and 1000 mg; 1000 mg of Nyale extract). After 2 h of fertilization incubation, the number of cell division phases (2–32 cells) was counted. The data were analyzed using ANOVA. RESULTS: The results of the GCMS test revealed that there were ten different compounds in the Nyale ethanol extract. There was a tendency for cleavage when testing the anti-mitotic potential of Nyale extract in each group. There was a significant difference in the percentage of cell changes in all treatments (control, 10 mg, 100 mg, and 1000 mg) (p < 0.005). CONCLUSION: Bioactive compounds found in marine worms (nyale) influence the percentage of cell division (anti-mitotic) in sea urchin embryos.